2008
DOI: 10.1007/s00595-007-3604-7
|View full text |Cite
|
Sign up to set email alerts
|

Low-pressure continuous suction of bile and pancreatic juice from the hepatic duct and jejunal limb after major hepatectomy with pancreatoduodenectomy

Abstract: We describe an effective technique for the low-pressure continuous suction of bile and pancreatic juice from the hepatic duct and jejunal limb after major hepatectomy with pancreatoduodenectomy (PD). After hepatectomy and PD, reconstruction is performed by a modification of Child's method. A pancreaticojejunostomy is completed with interrupted sutures between the pancreatic duct and mucosa, without inserting a stent. During hepaticojejunostomy, a 10-F silicone drain with side channels (Blake Silicone Drain; Et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Bile and pancreatic juice can be drained by a single drain. Even if bilioenteric anastomosis leaks, a 10-Fr intraluminal diameter of the anastomosis is maintained [3] . The treatment of stenotic bilioenteric anastomosis requires the long-term placement of a stent in the anastomosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bile and pancreatic juice can be drained by a single drain. Even if bilioenteric anastomosis leaks, a 10-Fr intraluminal diameter of the anastomosis is maintained [3] . The treatment of stenotic bilioenteric anastomosis requires the long-term placement of a stent in the anastomosis.…”
Section: Discussionmentioning
confidence: 99%
“…We also reported that a 10-Fr BLAKE Silicone Drain has been used as an external stent for a bilioenteric anastomosis during surgery for hepatic hilar malignancy [3] . This report describes a method for percutaneous transhepatic biliary stenting with a BLAKE Silicone Drain, and discusses the usefulness of placement of the drain connected to a J-VAC Suction Reservoir for the treatment of stenotic hepaticojejunostomy.…”
Section: Introductionmentioning
confidence: 95%
“…The anastomosis between the pancreatic remnant and the gastrointestinal tract after PD is the primary site of complications responsible for morbidity and mortality. 1,2 Symptomatic major leakage of the pancreatic anastomosis results in death in one-third to half of affected patients. 3 Postoperative pancreatic fi stula (POPF) has been reported to occur after 10%-29% of all PDs.…”
Section: Introductionmentioning
confidence: 99%
“…Occasionally, it is difficult to treat these conditions because of the occurrence of complicated anatomic changes after operative reconstruction. The best reconstruction method in the context of PD has been controversial, and several reconstruction methods exist, including a modified Child method (6)(7)(8). During the postoperative management associated with this modified Child method, pancreatic and biliary drainage tubes are guided outside of the body through the jejunal limb, and the blind end of the jejunal limb (BEJL) is surgically fixed to the abdominal wall (7,8).…”
mentioning
confidence: 99%
“…The best reconstruction method in the context of PD has been controversial, and several reconstruction methods exist, including a modified Child method (6)(7)(8). During the postoperative management associated with this modified Child method, pancreatic and biliary drainage tubes are guided outside of the body through the jejunal limb, and the blind end of the jejunal limb (BEJL) is surgically fixed to the abdominal wall (7,8). On the contrary, reconstruction during bile duct resection has been generally performed by using the Roux-en-Y method, during which biliary drainage tube insertion is guided by using the same method used for PD (9,10).…”
mentioning
confidence: 99%